2010
DOI: 10.1523/jneurosci.4659-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chondroitin Sulfate Proteoglycans in Axonal Conduction in Mammalian Spinal Cord

Abstract: Chronic unilateral hemisection (HX) of the adult rat spinal cord diminishes conduction through intact fibers in the ventrolateral funiculus (VLF) contralateral to HX. This is associated with a partial loss of myelination from fibers in the VLF (Arvanian et al., 2009). Here, we again measured conduction through the VLF using electrical stimulation while recording the resulting volley and synaptic potentials in target motoneurons. We found that intraspinal injection of chondroitinase-ABC, known to digest chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…Short latency, steep rising phase and negligible fluctuation in both latency and amplitude suggested that these responses were most probably monosynaptic, as previously discussed (Arvanian et al, 2009). Previous work indicates these connections are glutamatergic (Hunanyan et al, 2010(Hunanyan et al, , 2011. In the same animals, subsequent stimulation of the right lateral white matter at T6 gave rise to a long latency polyphasic EPSPs with a less steep rising phase in the same left L5 motoneurons, which were variable in shape and peak deflection ( Fig.…”
Section: Electrophysiological Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Short latency, steep rising phase and negligible fluctuation in both latency and amplitude suggested that these responses were most probably monosynaptic, as previously discussed (Arvanian et al, 2009). Previous work indicates these connections are glutamatergic (Hunanyan et al, 2010(Hunanyan et al, , 2011. In the same animals, subsequent stimulation of the right lateral white matter at T6 gave rise to a long latency polyphasic EPSPs with a less steep rising phase in the same left L5 motoneurons, which were variable in shape and peak deflection ( Fig.…”
Section: Electrophysiological Resultssupporting
confidence: 68%
“…The animals were deeply anesthetized and the spinal cords were exposed. L5 motoneurons were impaled with a sharp glass micropipette electrode and a tungsten sharp electrode was introduced at a depth of 1.3 mm, first in the right and then in the left LWM at T6 to stimulate descending spinal axons, as in previous experiments (Arvanian et al, 2009;Hunanyan et al, 2010).…”
Section: Electrophysiological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that chABC may modulate immune/inflammatory responses, liberate extracellular matrix-bound facilitatory factors, and overcome interactions between inhibitory CSPGs and extracellular matrix molecules in the injured CNS (reviewed in Crespo et al [85], Bradbury and Carter [86]). Attenuating the decline in axonal conduction through the SCI site could be involved [87]. Additionally, chABC may reduce growth inhibitory responses in neurons and provide neuroprotection by digesting chondroitin sulfate glycosaminoglycan chains that mediate the interaction between CSPGs and the neuron transmembrane receptor protein tyrosine phosphatase sigma [88,89].…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 99%
“…Initially, it was recognized that CSPGs inhibit axonal sprouting as they are one of the main obstacles to axon regeneration [16][17][18] . It is now clear that the action of CSPG is multifaceted, as an inhibitory effect of CSPGs on axonal conduction and synaptic transmission in adult rat spinal cord has been recently reported 19 .…”
mentioning
confidence: 99%